2002
DOI: 10.1161/hc5001.100528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on the Risk Stratification Using Stress Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging in Patients With Symptoms Suggestive of Coronary Artery Disease

Abstract: Background-Coronary artery disease can develop prematurely and is the leading cause of death among diabetics, making noninvasive risk stratification desirable. Methods and Results-Patients with symptoms of coronary artery disease who were undergoing stress myocardial perfusion imaging (MPI) from 5 centers were prospectively followed (2.5Ϯ1.5 years) for the subsequent occurrence of cardiac death, myocardial infarction (MI), and revascularization. Stress MPI results were categorized as normal or abnormal (fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(132 citation statements)
references
References 35 publications
7
124
1
Order By: Relevance
“…[30] Another study demonstrated that 8.6% of patients with diabetes had cardiac events (cardiac deaths and myocardial infarction) compared with 4.5% in the nondiabetic cohort. [12] The critical event rate seemed lower in our study as long as one-year interim results were observed. Even in our study, however, the incidence of sudden death, PCI, CABG, severe heart failure was in 3.6% of asymptomatic patients and cerebrovascular accident and transient ischemic attack in 1.4%.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…[30] Another study demonstrated that 8.6% of patients with diabetes had cardiac events (cardiac deaths and myocardial infarction) compared with 4.5% in the nondiabetic cohort. [12] The critical event rate seemed lower in our study as long as one-year interim results were observed. Even in our study, however, the incidence of sudden death, PCI, CABG, severe heart failure was in 3.6% of asymptomatic patients and cerebrovascular accident and transient ischemic attack in 1.4%.…”
Section: Discussioncontrasting
confidence: 43%
“…SPECT imaging was performed with standard acquisition protocols with 360 or 180-degree rotations. Gating was performed by 16,8,12 and 32 frames per cardiac cycle in 44%, 40%, 12% and 4% of the institutions. According to the preceding J-ACCESS substudy in patients with low-likelihood of ischemic heart disease and no events, EF with the 16-frame study was significantly higher than that with the 8-frame study by 4% only in men.…”
Section: Myocardial Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer SPECT techniques with ECG gating improve diagnostic accuracy in various patient populations, including women, diabetics, and elderly patients [23]. Adding information from a simultaneously performed calcium score using MDCT may further increase the accuracy [24].…”
Section: Perfusion Scintigraphymentioning
confidence: 99%
“…3 Myocardial perfusion imaging variables provide major incremental value for risk stratification in diabetic persons. 4 In this study diabetic women with ischemia in two or more coronary vascular territories had only a 60% 3-year survival free of cardiac death or nonfatal infarction. Diabetic men had a 79% event-free survival rate.…”
mentioning
confidence: 65%